Perception and buying behaviour of consumers towards FPOs food products in Tamil Nadu - MALARKODI, M; SIVAKUMAR, S D; PARASURAMAN, BALAJI; DIVYA, K; SHEELA, M SHANTHA; VIDHYAVATHI, A; SINGH, PARMINDER; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out to map the perception of consumers and to identify the factors influencing the consumer buying behaviour towards the food products of FPOs in Tamil Nadu. The results concluded that majority of the respondents purchased jaggery and sugar, cold pressed oil, snacks and millets category from the retail shops of FPOs. The quality and nutrient content were major product traits influencing consumers for purchasing the FPO food products. Most of the consumers felt that the quality and price of the food products were high in FPOs retail stores compared with other retail stores. So, FPOs should target high income people with high purchasing power who appreciate quality. Local people were purchasing the FPOs food products anytime. FPOs can devise effective marketing strategies to attract new customers from local and non-local customers. Most of the people have no awareness about FPOs retail outlets. Therefore, FPOs should pay attention in promoting their products and increasing the retail outlets for attracting the consumers and increasing the sales.